IMPLEMENTASI PENDIDIKAN TAUHID DALAM MEMBENTUK KARAKTER SANTRI PONDOK PESANTREN TAHFIDZUL QUR’AN IMAM AN NAWAWI BATAM: Implementasi Pendidikan Tauhid dalam Membentuk Karakter Santri Pondok Pesantren Tahfidzul Qur’an Imam An Nawawi Batam - Muhammad Hambal Shafwan; Muhammad Mahdi Abdullah (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2024)
This research is motivated by the problem of character crisis faced by the younger generation today. The formulation of the research problems are: (1) What is the character of the new students at Tahfidzul Quran Imam An-Nawawi Islamic Boarding School Batam?; (2) How is monotheism education at Tahfidzul Quran Imam An-Nawawi Islamic Boarding School Batam?; (3) What is the role of tauhid education at Tahfidzul Quran Imam An-Nawawi Islamic Boarding School in Batam in building the character of the students? This research is a qualitative research with a case study type. The results showed: (1) Tahfidzul Quran Imam An Nawawi Islamic Boarding School Batam is a boarding school that makes monotheism education the basis for building the character of students. Because, from the concept of monotheism, a very important standard will emerge in the concept of Islamic education, namely moral standards (value standards) whose essence is good and bad and right and wrong; (2) Tauhid education at Tahfidzul Quran Islamic Boarding School Imam An Nawawi Batam combines learning in the classroom and learning halaqah in the mosque; (3) Monotheism education in the classroom provides a broad and deep understanding of monotheism, while monotheism education through the halaqah method at the mosque is very useful in building the character of the students, including: (a) Educating the students independently; (b) There is closeness between teachers and students; (c) Effective in cultivating ukhuwah Islamiyah; (d) The blessing of knowledge because halaqah is done in the mosque.